FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PERUSAHAAN MANUFAKTUR GO PUBLIK JAWA TIMUR - Mr Slamet (BALANCE: Economic, Business, Management and Accounting Journal, 2014)
Based on the data available in Surabaya Stock Exchange, currently there are more than 130 listed manufacturing public companies all over Indonesia. About 30 of them are domiciled in East Java Province. As public companies, they are expected to get capital gain though right issues since in general they partly count on their working capital from external resources.The quistion in regard with the capitalization is how much of the portion of the  external capital to  be utilized to get  an  optimum capital costs. The optimum cost is supposed to contribute to optimum profit gaining for increasing the value of the company and the wealth of its stockholders persuant to its goals and objectives.This research was to identify the factors affecting the capital structure of public  manufacturing  companies  in  East  Java  Province.The  samples  were public manufacturing companies in East Java Province that had submitted their financial report year 2005 though 2009 to Surabaya Stock Exchange.The independent  factors  in  the  research  were  sales  stability,  assets  structure, growth  rate,  profitability,  cash  flow  and  firm  size.  The  data  gained  were analyzed by means of multiple regression method.Based on the results of statistical test, it showed that among the six independent factors, only profitability significantly and negatively affected the capital structure.Key words : Capital Structure, Sales Stability, Assets Structure, Growth Rate, Profitability, Cash Flow and Firm Size